Estágio Profissional: No tabuleiro de xadrez, a Rainha ensina e aprende em cada jogada. Relatório de - Ana Filipa Miranda Carvalho (2021)
This Internship Report is the name of this document and was developed in the second cycle of studies under the curricular unit of the Professional Internship (PI), which aims to obtain the degree of Master in Physical Education Teaching (PE) in Basic and Secondary Education. In this document I describe my learning, experiences and longings that I lived during the PI. In the PI all the learning and knowledge acquired during the graduation and the first year of the master's degree are put into practice and supervised by two specialised professionals, a Supervising Teacher (ST) from the College and a Cooperating Teacher (CT) belonging to the school. In this second year of the master's degree we were allowed to experience a PI which was characterised as one of the essential processes for moving the chess Queen in what would be her first great game. The Queen made several moves that tested her at various levels and traced the path of her construction and professional development. Thus, the document is divided into chapters, which portray an analogy of the chess game with my PI, which begins with the introduction, highlights the personal framework that refers to the history and characterization of the Queen, the institutional framework that details the board and the game pieces and the operational framework that describes all the conceptions, beliefs, problems encountered and strategies used throughout each move and ends with the conclusion and future perspectives of the Queen of chess. KEYWORD: